Antioxidant and inhibitory activity of Roselle Extract (Hibiscus sabdariffa L.) against Methicillin-Resistant Staphylococcus aureus (MRSA) - Nuril Fikriyah; Isnaeni Isnaeni; Asri Darmawati (Berkala Ilmiah Kimia Farmasi, 2021)
Background: Hibiscus sabdariffa known as roselle, which belongs to the family Malvaceae, grows in sub-tropical and tropical region including Indonesia. Several studies have reported the benefits of roselle for health. Roselle extract has been shown to have antibacterial effect as a support for antibacterial therapy, especially for case of antibiotic resistance, and antioxidant effect which can neutralize free radicals. Purpose: The aim of this study was obtaining the minimum inhibitory concentration (MIC) and inhibition concentration (IC50) of roselle extract. Methods: Antibacterial effect of roselle extract against Methicillin-Resistant Staphylococcus aureus (MRSA) was tested in nutrient agar media using diffusion method. Antioxidant activity of roselle extract was performed by DPPH. The violet color of DPPH solutions that was reduced by roselle extract were measured using visible spectrophotometer at the wavelength of 516 nm. Result: The result of this study obtained the (MIC) and IC50 of roselle extract were 2,5% and 1251±202,32 ppm, respectively. Conclusion: It can be concluded that roselle extract have antibacterial effect against MRSA and antioxidant effect.